2011
DOI: 10.1007/s00348-011-1250-8
|View full text |Cite
|
Sign up to set email alerts
|

Near-wake flow structure downwind of a wind turbine in a turbulent boundary layer

Abstract: Wind turbines operate in the surface layer of the atmospheric boundary layer, where they are subjected to strong wind shear and relatively high turbulence levels. These incoming boundary layer flow characteristics are expected to affect the structure of wind turbine wakes. The near-wake region is characterized by a complex coupled vortex system (including helicoidal tip vortices), unsteadiness and strong turbulence heterogeneity. Limited information about the spatial distribution of turbulence in the near wake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
122
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(152 citation statements)
references
References 34 publications
(49 reference statements)
22
122
0
1
Order By: Relevance
“…On the other hand, no signature of the tip vortex remains visible at x/D = 3, even for the low turbulent inflow conditions. These results are consistent with Zhang et al [23,24] works. They showed that the tip vortex signatures are not distinguishable anymore from x/D = 3 in a neutral or convective incoming boundary layer with a turbulence intensity of 8% at hub height.…”
Section: Tip-vortex Signature Persistencesupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, no signature of the tip vortex remains visible at x/D = 3, even for the low turbulent inflow conditions. These results are consistent with Zhang et al [23,24] works. They showed that the tip vortex signatures are not distinguishable anymore from x/D = 3 in a neutral or convective incoming boundary layer with a turbulence intensity of 8% at hub height.…”
Section: Tip-vortex Signature Persistencesupporting
confidence: 93%
“…It shows that, if the ambient turbulence level is high enough, the turbulent diffusion, responsible of the turbulence mixing, destroys the coherence of the rotational flow. These results are consistent with Zhang et al, 2012 [23], who obtained similar conclusions in a neutral incoming boundary layer with a turbulence intensity of 8% at hub height.…”
Section: Rotational Momentum Persistencesupporting
confidence: 93%
“…However, since full-scale operating turbines are placed inside the atmospheric boundary layer, the influence and effects of a boundary layer inflow are important research topics. [2] studied the near wake structure of a wind turbine placed in a neutral boundary layer flow. The model was placed in the lowest one-third of the boundary layer, and both Particle Image Velocimetry (PIV) and hot-wire measurements were performed up to 5 downstream diameters (using PIV) and 20 downstream diameters (using hot-wire).…”
Section: Introductionmentioning
confidence: 99%
“…Medici and Alfredsson (2006), Agel (2009), Zhang et al (2012)) and numerical simulations (e.g. Troldborg et al (2007), Wu and Porté-Agel (2012)) of wind turbines, the inflow wind field a wind turbine is exposed to strongly influences the wake structure and the turbine loading, both affecting the power production of a wind turbine.…”
mentioning
confidence: 99%
“…There are experimental studies considering different atmospheric stratifications (NBL, SBL, CBL) (e.g. Medici and Alfredsson (2006), Chamorro and Porté-Agel (2010), Zhang et al (2012), Tian et al (2013), Zhang et al (2013)). In most of the numerical simulations of an individual wind turbine, however, an NBL is assumed (e.g.…”
mentioning
confidence: 99%